Hubungan Minat Belajar dengan Hasil Belajar Pendidikan Agama Islam pada Siswa Kelas IV–V SDN 4 Kertasari Kecamatan Ciamis - Daryaman Daryaman; Dede Darisman; Yelia AhyaRobby; Kholilur Rohman (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the correlation between learning interest and Islamic Religious Education learning outcomes among 4th and 5th-grade students at SDN 4 Kertasari, Ciamis District. This study used a quantitative approach with a correlational design. The population comprised 52 students, all of whom were included as the sample through total sampling technique. Data on learning interest were obtained using a questionnaire, while data on learning outcomes were collected through the documentation of Islamic Religious Education grades. Data analysis was performed using descriptive and inferential statistics with IBM SPSS Statistics version 29. The normality test indicated that the data were not normally distributed; thus, hypothesis testing was conducted using Kendall's tau-b correlation. The results showed a correlation coefficient of 0.052 with a significance value of 0,614 (p > 0,05). These findings indicate that there is no significant correlation between learning interest and Islamic Religious Education learning outcomes among 4th and 5th-grade students at SDN 4 Kertasari, Ciamis District. The results imply that learning outcomes are influenced not only by learning interest, but also by various other factors, such as learning motivation, prior ability, family environment, learning strategies, and school environmental support. This study suggests that efforts to improve Islamic Religious Education learning outcomes need to be carried out through a comprehensive approach by considering various factors that affect students' learning success.